Rare bird documentation form for Greater Scaup south of Council Bluffs, 1982 - Moore, Francis L.et al (1982)
Rare bird documentation form for a Greater Scaup south of Council Bluffs in Mills County, IA on March 28, 1982. Epson - sheet feed